The Effect of a Combination of Turmeric Rhizome Extract (Curcuma longa L.) and Temulawak Rhizome Extract (Curcuma xanthorrhiza R.) on the Mortality of Grayak Caterpillar Pests (Spodoptera litura F.) - Sopian, Noer Dhevie; Lumowa, Sonja V.T.; Masitah, Masitah; Tindangen, Makrina (Edumaspul: Jurnal Pendidikan, 2025)
Determine effect of a combination of turmeric rhizome extract (Curcuma longa L.) also temulawak (Curcuma xanthorrhiza R.) on the mortality of Spodoptera litura F.. The experiment used a CRD with five treatment concentrations (0%, 35%, 40%, 45%, and 50%), each replicated five times. Mortality data were analyzed using one-way ANOVA followed by LSD test. Combination of turmeric and temulawak extracts significantly affected armyworm mortality, with the highest mortality rate of 80% observed at a 50% concentration. These findings suggest that plant-based pesticides derived from turmeric and temulawak have potential as an eco-friendly pest control alternative.